Insiden gejala menetap dan gambaran ekokardiografi pasca infensi COVID-19 ringan - Almazini, Prima; Soesanto, Amiliana M; Kuncoro, Ario S; Ariani, Rina; Rudiktyo, Estu; Sukmawan, Renan (Jurnal Kardiologi Indonesia, 2022)
Background:Survived from COVID-19 infection, some patients yet have residual symptoms. Multi-organ and mechanisms of disease can be involved. The data regarding echocardiographic dimension and function of the cardiac in the COVID-19 survivors remains scarce. Method:This was a descriptive cross-sectional study that involves a total of 63 subjects. Subjects were employees and medical residents at National Cardiovascular Center Harapan Kita, who previously get infected by COVID-19. Each subject was examined transthoracic echocardiography once at the time of recruitment. Echocardiographic parameters obtained in this study included dimension and systolic function of the left ventricle and right ventricle, global longitudinal strain by 2D speckle tracking echocardiography, and myocardial work index. Result:More than a half of the subjects experienced persistent symptoms after recovery from COVID-19 infection and mainly was fatigue (33.3%). The timing of data acquisition on the median was 32 days after the negative of the COVID-19 test result. 2D echocardiography measurement of left ventricle indicated mean of end-diastolic diameter and end-systolic diameter was 45 mm and 27 mm, respectively. The mean ejection fraction (EF) of the left ventricle by Simpson’s biplane method was 61%. The median of tricuspid annular plane systolic excursion (TAPSE) parameter was 23 mm and the fractional area change (FAC) parameter was 39%. The mean of global longitudinal strain (GLS) was -19.6%. Conclusion:After recovery from COVID-19 infection, some survivors may have post-acute infectious consequences of COVID-19 such as fatigue, dyspnea, and malaise. However, echocardiographic findings in those patients with mild symptoms, including 2D echocardiography, myocardial strain analysis, and myocardial work index, indicate normal dimension and systolic function in both left ventricle and right ventricle.This article has a related Erratum.